Understanding and Addressing Demotivation in English Learning: Insights from Elementary School Students and Their Homeroom Teacher - Andriani, Riza Oktavia; Rusfandi Rusfandi; Oktavia Widiastuti (English Teaching Journal : A Journal of English Literature, Language and Education, 2024)
This study aims to identify the external factors that contribute to the demotivation of elementary school students in learning English as a foreign language and to examine the efforts employed by the teacher to mitigate this demotivation. Employing qualitative descriptive methods, data were collected through questionnaires administered to twenty fourth-grade students and through interviews with their homeroom teacher. Furthermore, observations were undertaken to evaluate how the teacher's initiatives to reduce student demotivation corresponded with actual classroom dynamics. The results indicated that inadequate school facilities, low test scores, non-communicative teaching methods, unengaging learning content and materials, as well as the teacher's competence and teaching styles, were the primary factors contributing to decreased student motivation. Among these factors, inadequate school facilities and low test scores exerted the most significant influence. The external factors that the teacher has addressed in an effort to prevent further demotivation encompass teacher competence and teaching style, learning content and materials, and non-communicative methods. These findings suggest that enhancements in educational facilities, improvements in teaching methodologies, and the creation of more engaging learning materials can contribute to reducing demotivation and increasing students' motivation to learn English. This study offers valuable insights for educators and policymakers in the development of effective learning strategies for English at the elementary level.